Chad : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1996)
This paper reviews economic developments in Chad during 1990-95. After a noticeable deterioration during 1991-93, Chad's economy rebounded in 1994 following the devaluation, and continued to expand in 1995. During 1991-93, economic and financial developments were characterized by persistent domestic and external imbalances, which negatively affected economic growth and increased poverty. Real GDP and import volumes stagnated, export volumes dropped by 12 percent, and the terms of trade declined by 11 percent; investment remained low, barely averaging 10 percent of GDP, and real consumption per capita declined by 15 percent.